Structural changes in Western Visayas demographic and distributional aspects. - Losare, Andrei C. III
Structural transformation of the economy is one of the goals of development. This transformation involves changes in the structure of demand, productivity, production, labor force, employment conditions and demographic transition. (p)This study focuses on the patterns of structural changes (demographic and distributional aspects) and the macroeconomic policies that brought about such changes in Western Visayas. Data on labor allocation, employment conditions, urbanization, demographic transition, income distribution, and poverty incidence from the year 1970 to 1998 are examined. These data are used to provide comprehensive picture of the distributional and demographic aspects of structural changes in Western Visayas. (p)The study shows that there was no significant and sustained structural change that happened, thus, economic development in Western Visayas remained stagnant during the period covered by the study. This is evidenced by the insignificant sectoral shifts from agriculture towards less resilient services sector. In contrast, the experience of Newly Industrialized Countries (NICs) shows that the labor shed off by the agricultural sector was absorbed by the manufacturing sector, which is one of the needed prerequisites for a genuine structural change. Moreover, the data on population, income distribution, and poverty also failed to show significant improvement. (p)Also included in the study is a discussion of the trade and industrial policies that led to the aforementioned trend. Fiscal deficits, and high investment and infrastructure spending characterized the 1970's. This led to the debt-driven growth, mainly owed to bilateral and multilateral sources. There was a continued emphasis on import substitution, which led to an over-emphasis on large-scale capital-intensive manufacturing at the expense of the manufactured exports and the development of more labor-intensive or medium and small-scale enterprises. These and the succeeding policies resulted in constrained growth in the regions.